Systematic Literature Review: Analysis the Implementation of the 5E Learning Cycle in Learning Chemistry - Siska Juita Berlian Putri Gea; Wiji Wiji; Tuszie Widhiyanti (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the implementation of the 5E (Engage, Explore, Explain, Elaborate, and Evaluate) learning cycle in chemistry learning, to analyze multiple representations (macroscopic, submicroscopic, and symbolic) as characteristics of chemistry, and to identify learning outcomes. This study was conducted using a Systematic Literature Review (SLR) in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A total of 38 articles from Google Scholar from 2020 to 2026 were analyzed based on the determined inclusion criteria.  The results show that the implementation of the 5E learning cycle in chemistry learning has been widely applied across various topics in chemistry. Although various levels of representation have been used, the relationship between macroscopic, submicroscopic, and symbolic representations is still limited in these articles. Findings also indicate that cognitive learning outcomes are the most frequently reported, particularly conceptual understanding and academic achievement. Several studies also explored affective outcomes and other skills, which indicate a more diverse range of learning outcomes. Overall, the evidence suggests that the 5E learning cycle contributes positively to chemistry learning